Laboratory Intercomparison of Cytogenetic Dosimetry Among 38 Laboratories in China - Yan Pan; Jianlei Ruan; Gang Gao; Lina Wu; Chunnan Piao; Jianxiang Liu (SAGE Publishing, 2019)
A nationwide intercomparison exercise for estimating the irradiated dose was organized by the National Institute for Radiological Protection, Center for Disease Control and Prevention of China. Thirty-eight laboratories participated in this program. The main objective of this intercomparison exercise was to compare the participants' ability of operation and dose assessment basing on the frequencies of dicentrics and centric rings. Whole blood samples were irradiated with different dosages of 60 Co γ-rays. Each laboratory collected 2 blind samples and prepared the slides independently. All participants presented the estimated dose reports within 30 days. The doses assessed by the participants were acceptable within the reference dose of ±20%. The mean absolute difference of estimated dose relative to the reference dose was calculated, which reflected the overall accuracy of dose estimates for each laboratory. The overall estimation results of blind blood samples for intercomparison showed a good agreement with the reference dose for each sample, with nearly 75% of the participants producing acceptable results.